Process Evaluations for the Scale-Up of Complex Interventions – a Scoping Review - Lekha Rathod; Martin Heine; Daniel Boateng; Monika Martens; Josefien van Olmen; Grace Marie Ku; Kerstin Klipstein-Grobusch (International Journal of Integrated Care)
Introduction: Complex health interventions (CHIs) are common in (public) health and social care practice and policy. A process evaluation (PE) is an essential part of designing and testing CHIs and questions what is implemented, the mechanisms of change, and how context affects implementation. The scale-up of CHIs is challenging and heterogeneous, making the accompanying PE unique to the nature of the inquiry. Methods: We conducted a scoping review to describe the current practice of conducting PEs alongside or following the scale-up of CHI. Eight primary data sources were searched and data extracted on study characteristics, intervention characteristics, methods used in relation to the PE, and stakeholders included. Results: We reviewed 10,538 records and included 56 studies. Seven common thematic areas emerged in which CHIs were being scaled-up. The use of scale-up specific frameworks was rare, and common outcomes of the process evaluation focussed on barriers and facilitators in relation to the context; often obtained “once-off” using qualitative and quantitative data sources. Scale-up strategies reported were: supporting increased coverage, comprehensiveness, and institutionalisation; often simultaneously. Conclusion: Variations in the conduct of process evaluations during the scale-up phase of complex health interventions may reflect differences in context, conceptual challenges, the multi-dimensional nature of scale-up, and the point of engagement with the health care system (e.g., community-level). Ideally, a process evaluation is a recurrent continuous process, leveraging a systems-driven understanding and triangulation of qualitative and quantitative data, that takes place alongside the scale-up project to inform real-world adaptations of scale-up strategies and (untoward) mechanisms of impact when applicable.